2019
DOI: 10.4067/s0718-221x2019005000208
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of thermally modified short and long rotation teaks and the effects on coatings performance

Abstract: Many wood processing industries use short rotation teak, which has lower quality especially in durability and dimensional stability. Heat treatment is an eco-friendly method to improve dimensional stability and durability of wood. The objectives of the study were to investigate the effects of thermal modification on chemical composition, colour, dimensional stability and durability as well as coating's performance after accelerated weathering of short and long rotation teak for exterior utilization. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 43 publications
0
34
1
1
Order By: Relevance
“…When analyzing the chemical constituents of the teakwood Chagas et al (2014) and Pratiwi et al (2019) found lower extractives content (4,76% and 7,41 %), higher insoluble lignin content (30,43% and 32,57 %) and holocellulose content (64,01% and 67,42 %) to the values of the untreated teakwood in the present study.…”
Section: Chemical Constituentscontrasting
confidence: 41%
See 3 more Smart Citations
“…When analyzing the chemical constituents of the teakwood Chagas et al (2014) and Pratiwi et al (2019) found lower extractives content (4,76% and 7,41 %), higher insoluble lignin content (30,43% and 32,57 %) and holocellulose content (64,01% and 67,42 %) to the values of the untreated teakwood in the present study.…”
Section: Chemical Constituentscontrasting
confidence: 41%
“…After the heat treatment at 220 °C for 20 h Pratiwi et al (2019) found a mean holocellulose reduction of 15,18% and total extractives of 21,32%, while an increase in lignin content of 31,3% occurred. While in this work an increase in total extractive content (48,59%) and lignin (26,44%) and a reduction in holocellulose content of 19,84% were found.…”
Section: Chemical Constituentsmentioning
confidence: 91%
See 2 more Smart Citations
“…Alternative technologies are able to change the chemical structure of wood and improve its biological resistance (Klüppel et al 2015, Treu & Larnøy 2016. Thermal modification has provided improved decay resistance, dimensional stability, weathering resistance, reduced water absorption, material darkening and colour stability (Silva et al 2015, Sivrikaya et al 2015, Pratiwi et al 2019) in many species of wood.…”
Section: Introductionmentioning
confidence: 99%